How to build a successful international Web site - Bishop, Mark, 1956- (Coriolis Group Books, 1998)
How To Build A Successful International Web Site provides the information you need to go multilingual. You will learn to create cool international Web sites, use HTML in every language, find and use multilingual Web translation services and products, manage software to display in foreign languages, submit URLs to international search engines, and avoid cross-cultural faux pas. You'll also find plenty of international business information, references, links, an the tools you'll need to make your Web site multilingual.